Perancangan Aplikasi QR Code Pendaftaran Perizinan Berbasis Android Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Bandar Lampung - Ferry Susanto; Khozainuz Zuhri; Fatimah Fahurian; Romi Hendri (Universitas Mitra Indonesia, 2022)
Based on the research, it is necessary to have an information media that is quite effective of the public registering permits in Bandar Lampung City. The purpose of the research is to make it easier for applicants who register their licenses of permits at Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Bandar Lampung. So the author makes a solution by making a mobile application with a report entitled